Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/app.23804
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and structural characterization of POSS‐modified polyamide 6

Abstract: This work investigated the mechanical behavior of POSS-modified polyamide 6 (PA6), containing PA6 chains terminated at one end with aminopropyl-heptaisobutyl POSS. Three systems with different POSS contents (5.4, 10.8, and 16.2 wt %), each characterized by a specific molecular mass, and the corresponding PA6 neat polymers were examined. The materials were first subjected to morphological and calorimetric analysis by wide-angle X-ray diffraction and differential scanning calorimetry, respectively. Tensile tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
(30 reference statements)
1
31
0
Order By: Relevance
“…Th e spherical morphology of msib-POSS aggregates was indicative that the phase separation took place during the cooling of POM/msib-POSS composites. Similar eff ects were reported for other POSS-polymer systems [35,36].…”
Section: Pom Nanocomposites With Poss Nanoparticlessupporting
confidence: 72%
“…Th e spherical morphology of msib-POSS aggregates was indicative that the phase separation took place during the cooling of POM/msib-POSS composites. Similar eff ects were reported for other POSS-polymer systems [35,36].…”
Section: Pom Nanocomposites With Poss Nanoparticlessupporting
confidence: 72%
“…[1] During the last decades a high number of reports about polymeric POSS nanocomposites partly reviewed [2,3] have been published by different authors also dealing with POSS-modified polyurethane (PU) materials. [4][5][6][7][8][9][10][11][12] Some contributions are available which give information about the bulk mechanical properties of POSS nanocomposites outside the deformation range of linear response such as stress-strain behaviour at tensile loading, [6,8,[13][14][15][16][17][18][19] flexural behaviour at three-point bending test [20,21] or fracture behaviour. [7,16,22] Incorporation of POSS molecules into PU leads to an improvement in elastic modulus [6,8] but a decreasing ductility, [6] which can be attributed to the attachment of rigid POSS molecules at the molecular level and the improved miscibility between the hard and soft segments.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of POSS cages into polymeric materials may result in dramatic improvements in polymer properties, including in the upper use temperature, oxidative resistance, and surface hardening, leading to improved mechanical properties and a reduction in flammability. [7][8][9][10] Rafailovich and coworkers 11 have found that random copolymers functionalized with POSS groups can be very efficient at compatibilizing immiscible polymer blends. This compatibilization was proposed to be due to increases in site functionality provided by the POSS molecule, without the entropic penalty associated with functionalities grafted directly onto the polymer chains.…”
Section: Introductionmentioning
confidence: 98%